(untitled) (Brazilian Journal of Radiation Sciences, 2023)
Due to its vast number of occurrences, cancer has caused an economic impact on the public and supplementary health care sectors. It is estimated that more than 50% of patients diagnosed with malignant neoplasms need radiotherapy at some stage of their treatment, most of them treated with photon and/or electron beams. Due to the build-up effect (increase in dose in the matter from deposition on the surface to a point of maximum dose) caused by the interaction of photon beams with the irradiated tissue, bolus is often used in routine radiotherapy sectors to superficialize the point of maximum dose in the treatment region. The human body has complex surfaces that are often treatment regions in radiotherapy, but commercial bolus with a standard shape and length do not adapt perfectly to these surfaces. When this happens, air gaps may appear in the region, causing differences between the dose defined in radiotherapy planning and the dose delivered during treatment. In order to eliminate these air gaps and possible dose distribution errors, two methodologies for individualized bolus construction were proposed. In both cases, computed tomography images of the Alderson Rando male anthropomorphic phantom were used as a reference of the anatomy of a human body. From these images, one bolus model was constructed in the 3D modeling software 3ds Max by creating a polygonal mesh, while the other bolus model was constructed in the image computing software 3D Slicer, using segmentation tools. The software Creality Slicer 1.2.3. prepared the files for 3D printing. The prints of the files were made on polylactic acid filament on the Tevo Tarantula Pro printer. The bolus construction methodology using the software 3ds Max showed better results, as a greater contact area between the bolus and the phantom was observed when testing the fit of the printed bolus to the physical phantom. The 3D files of the virtual bolus will be available for future computer simulations. The printed bolus could be used in dosimetry with linear accelerators.